2017
DOI: 10.3389/fneur.2017.00182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 10 Hz Repetitive Transcranial Magnetic Stimulation of the Left Dorsolateral Prefrontal Cortex in Disorders of Consciousness

Abstract: BackgroundWhile repetitive transcranial magnetic stimulation (rTMS) has been applied in treatment of patients with disorders of consciousness (DOC), a standardized stimulation protocol has not been proposed, and its therapeutic effects are inconsistently documented.ObjectivesTo assess the efficacy of rTMS in improving consciousness in patients with persistent minimally conscious state (MCS) or unresponsive wakefulness syndrome (UWS), previously known as vegetative state (VS).MethodA prospective single-blinded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 38 publications
6
69
0
4
Order By: Relevance
“…The effect of 20 sessions of 10Hz DLPFC rTMS (each session lasting 11 minutes) was evaluated in 16 patients with DOC (3-35 months post-injury) in a single-blind uncontrolled study. 50 CRS-R total score increased in all 5 patients in MCS and in 4/11 patients with UWS, and the improvements were more important in MCS patients. In a small sample open-label study, 10 post-anoxic patients with UWS (4-15 months post-onset) received a single session of DLPFC 10-Hz rTMS for 60 minutes.…”
Section: Repeated Transcranial Magnetic Stimulationmentioning
confidence: 83%
See 1 more Smart Citation
“…The effect of 20 sessions of 10Hz DLPFC rTMS (each session lasting 11 minutes) was evaluated in 16 patients with DOC (3-35 months post-injury) in a single-blind uncontrolled study. 50 CRS-R total score increased in all 5 patients in MCS and in 4/11 patients with UWS, and the improvements were more important in MCS patients. In a small sample open-label study, 10 post-anoxic patients with UWS (4-15 months post-onset) received a single session of DLPFC 10-Hz rTMS for 60 minutes.…”
Section: Repeated Transcranial Magnetic Stimulationmentioning
confidence: 83%
“…45,46,48 Future RCTs should target the DLPFC, similarly to tDCS, as two uncontrolled observational rTMS studies show some positive effects. 50,51 Demographic and clinical characteristics of responders should also be investigated in larger RCTs or meta-analyses. Others brain areas could also be targeted according to patients' brain lesions and neural residual function since patients' clinical responsiveness seems to depend on this.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many studies have used DTT to show improvements in impaired consciousness concurrent with ARAS injury recovery in patients with disorder of consciousness (DOC) [5][6][7][8][9]. It has been widely reported that repetitive transcranial magnetic stimulation (rTMS) has a therapeutic effect on impaired consciousness in patients with DOC [10][11][12]; however, little has been reported on the direct effect of rTMS on the ARAS.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of using NIBS to highlight neural patterns potentially subtending awareness relies on the fact that awareness recovery requires that neuroplasticity mechanisms reach a determined threshold for awareness to emerge [131]. This issue was well evidenced by several experimental approaches, including the assessment of EEG oscillatory microstate occurrence (fast alpha and theta/delta), and brain operational architectonics (size, instability, speed of growth, and life span of neuronal assemblies; number and strength of connections; and strength of the DMN synchrony) [132][133][134][135][136][137][138][139][140][141]. Indeed, NIBS can furnish the required, still missing amount of neuroplasticity allowing awareness to emerge, even transiently [37,[76][77][78].…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%